Acquiring sectional profile of metro tunnels using charge-coupled device cameras. Issue 9 (1st September 2016) - Ai, Qing; Yuan, Yong; Bi, Xiangli
Abstract: Timely acquiring deformation of sectional profile is a proactive maintenance activity for ensuring the safety of tunnels. Metro tunnels, especially constructed by shield tunnelling method, are long span infrastructures need to inspect their deformations at many different positions. This is a vast amount of work if carried by traditional approaches manually. Some advanced technologies, such as terrestrial laser scanning, are also unable to carry out the work quickly and economically. However, only severe deformations that may lead to emergency action are required to be detected timely. Thus, the urgent demands for acquiring sectional profile of metro tunnel should be of fast in operation, accuracy under tolerable acceptance and competitive with cost efficient. This paper focuses on the method of acquiring sectional profile of metro tunnels by a cart equipped with charge-coupled device cameras. The geometric features of sectional profile are extracted from images by a series of algorithms based on photogrammetry. Using this method, the speed of acquisition is improved no less than 5 km/h with acceptable accuracy. An on-site application validates that this method is sufficient for screening out severe deformations in metro tunnel.